Sex-Based Differences in pH Parameters and Esophageal Impedance of Patients With Gastroesophageal Reflux Disease - Ye, Bixing; Wang, Yanjuan; Lin, Lin; Jiang, Liuqin; Wang, Meifeng (Frontiers in Medicine, 2021)
Background/Aims: The incidence of reflux esophagitis (RE) has a striking predominance in males. Conversely, non-erosive reflux disease (NERD) is more common in females. This imbalance of gastroesophageal reflux disease (GERD) implies sex-related differences in its pathogenesis. However, limited studies have analyzed the sex-based differences in pH parameters and esophageal impedance of GERD patients. Methods: This study evaluated sex-based pathogenesis differences by comparing reflux episodes, mean nocturnal baseline impedance (MNBI) values, and post-reflux swallow-induced peristaltic wave (PSPW) index values of males with GERD and females with GERD using 24-h multichannel intraluminal impedance and pH monitoring. Results: We analyzed 181 patients (102 males and 79 females) with GERD. Reflux symptom index (RSI) scores were higher in females than that in males (P < 0.05). Males had significantly longer acid exposure times, higher DeMeester scores, and more acid reflux episodes than females (P < 0.05). Females had more instances of weakly acidic reflux than males (P < 0.01). The PSPW index values of males and females were similar (P > 0.05). Compared with females, males had lower MNBI values for the mid and distal esophagus (P < 0.05). However, with increasing age, the MNBI values of females decreased more rapidly than those of males. MNBI values of elderly patients of both sexes older than 60 years were similar. Conclusions: Acid reflux is more likely to occur in males; however, females tend to have more instances of weakly acid reflux. The integrity of the esophageal mucosa is more fragile in males than in females; however, the esophageal mucosal barrier attenuates more rapidly with increasing age in females than in males.